Pediatric audiology casebook - Madell, Jane Reger; Flexer, Carol Ann; Wolfe, Jace; Schafer, Erin C. (Thieme Medical Publishers, 2020)
"Leverages real-life cases to foster in-depth understanding of pediatric audiology. Pediatric Audiology Casebook, Second Edition is fully updated with more than 60 new cases presented in four sections, covering all facets of the diagnosis and management of hearing disorders in children. Renowned experts Jane R. Madell, Carol Flexer and rising stars Jace Wolfe and Erin C. Schafer have compiled an impressive compendium of basic to complex diagnostic cases, covering the most salient topics in the field. The book effectively bridges the gap between content knowledge and clinical application, enabling readers to put acquired theory into active practice by engaging in problem-based learning. Key Features - All cases include key information for diagnosing and managing pediatric patients : clinical history, audiologic testing, evaluative reader questions, thought-provoking answers, definitive diagnosis, recommended treatment options, and final outcome - Expanded use of cochlear implants including implant performance issues - Overcoming challenges from family non-compliance and complicated mapping to professional collaboration and multidisciplinary assessments. Paired with the best-selling textbook Pediatric Audiology: Diagnosis, Technology, and Management, Third Edition, this robust classroom duo is an essential resource for instructors and students alike. Acquire in-depth knowledge from the textbook, apply it to practical case studies, and achieve deeper understanding of the full spectrum of pediatric audiology"--Provided by publisher.